Teachers' Reactions to Educational Television Programs during the Pandemic and Their Implied Images of Mathematics Teaching - Konstantinos Tatsis; Bożena Maj-Tatsis (MDPI AG, 2023)
In this paper, we discuss the images of mathematics and its teaching, as expressed by mathematics teachers, in reaction to educational programs broadcasted by Polish public television channels during the first lockdown in 2020. For our analysis, we deployed a theoretical framework mostly drawn from the work of Paul Ernest. Our data came from a variety of sources such as educational fora, social networks, websites and email exchanges. Our results, based on an interpretative analysis, revealed four overarching images of mathematics and its teaching which, although related to the specificities of television, resembled images found by other relevant studies. The first image of mathematics views it as an unambiguous discipline in which there is no room for more than one point of view. The second image refers to the teacher as a presenter who is expected to possess particular verbal and non-verbal skills, especially given the fact that the television programs did not involve any live audiences. The third image refers to the unappealing nature of the broadcasted lessons, while the fourth image refers to the underlying approach of crude memorization associated with 'traditional' mathematics teaching. Our study's contribution is twofold: in the improvement of televised educational programs (and possibly online courses) and in the improvement of the public's image of mathematics.